2006
DOI: 10.2341/05-132
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Microleakage in MOD Restorations: In Vitro Comparison of Indirect and Direct Composite

Abstract: Clinical RelevanceOne of the advantages reported for indirect composite restorations is the reduction of polymerization shrinkage, which could produce better marginal sealing. Although sealing of cervical enamel margins was slightly better for the indirect systems used, no difference between indirect and direct restorations was found for cervical margins in cementum/dentin. SUMMARYThis study compared microleakage between indirect composite inlays and direct composite restorations. Forty-eight standard inlay MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 16 publications
(17 reference statements)
1
36
0
2
Order By: Relevance
“…5 SEM examination of gap formation at the cervical wall showed good marginal adaptation for all groups tested after 24 hours. It has been reported that initial bonding resistance 29 and initial marginal adaptation 25 are adequate with new adhesive systems, especially when the margins are located in enamel. 30 In fact, the interlocking formed by penetration of the adhesive system inside the microgaps originated by acid etching in highly mineralized enamel has been reported to be a more secure, stable bonding than adhesion obtained with dentin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 SEM examination of gap formation at the cervical wall showed good marginal adaptation for all groups tested after 24 hours. It has been reported that initial bonding resistance 29 and initial marginal adaptation 25 are adequate with new adhesive systems, especially when the margins are located in enamel. 30 In fact, the interlocking formed by penetration of the adhesive system inside the microgaps originated by acid etching in highly mineralized enamel has been reported to be a more secure, stable bonding than adhesion obtained with dentin.…”
mentioning
confidence: 99%
“…In a recent study, better marginal sealing was observed for indirect composite restorations in enamel when compared to direct composite restorations. 25 The bevel was also applied in order to produce a long lasting adhesive interface and, based on observations from this study, beveled restorations generally exhibited better fracture resistance and less gap formation initially and after six months.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microleakage may result from many factors, including adaptation of resin material to the tooth surface, the adhesive system used, and polymerization shrinkage of materials used. 20,21 Dye penetration is one of the most frequently used methods to evaluate microleakage. 21,22 In the current study, a dye penetration test was used because it is simple and relatively cheap and provides quantitative and comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Dye penetration is one of the most frequently used methods to evaluate microleakage. 21,22 In the current study, a dye penetration test was used because it is simple and relatively cheap and provides quantitative and comparable results. This method does have some limitations, however, such as subjectivity of reading and high diffusability of dyes due to their low molecular weight.…”
Section: Discussionmentioning
confidence: 99%